2001
DOI: 10.1046/j.1523-1755.2001.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemic renal failure in mice: Role of tumor necrosis factor independent of inducible nitric oxide synthase

Abstract: These results demonstrate a role of TNF in the early renal dysfunction (16 h) in a septic mouse model independent of iNOS, hypotension, apoptosis, leukocyte accumulation, and morphological alterations, thus suggesting renal hypoperfusion secondary to an imbalance between, as yet to be defined, renal vasoconstrictors and vasodilators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
129
0
3

Year Published

2002
2002
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(148 citation statements)
references
References 23 publications
16
129
0
3
Order By: Relevance
“…However, apart from increasing MAP, this selective inhibitor of iNOS offered little advantage to the kidneys as compared with saline resuscitation (64). In agreement, the degree of renal failure after LPS infusion was similar in iNOS knockout mice as compared with wild-type mice (43).…”
Section: Inhibition Of Nitric Oxide Synthasesupporting
confidence: 54%
See 1 more Smart Citation
“…However, apart from increasing MAP, this selective inhibitor of iNOS offered little advantage to the kidneys as compared with saline resuscitation (64). In agreement, the degree of renal failure after LPS infusion was similar in iNOS knockout mice as compared with wild-type mice (43).…”
Section: Inhibition Of Nitric Oxide Synthasesupporting
confidence: 54%
“…Specifically for the kidney, passive immunization to TNF-␣ prevented renal cortical damage during endotoxemia in rhesus monkeys (42). Neutralization of TNF-␣ with a TNF-soluble receptor protected mice against LPS-induced renal failure (43). Mice with a targeted deletion of TNF receptor-1 (TNFR1 Ϫ/Ϫ ) were resistant to LPS-induced renal failure (44).…”
Section: Specific Pharmacologic Treatmentmentioning
confidence: 99%
“…Endotoxemia, a major component of sepsis, is associated with an increase in inducible NO synthase (6,7,8,16). In the mouse model used in the present study, a significant rise in plasma NO has been demonstrated at 16 h, and this increase in NO does not occur in inducible NO synthase knockout mice (7).…”
Section: Discussionmentioning
confidence: 56%
“…A significant decrease in glomerular filtration rate (GFR) and renal blood flow (RBF) occurs in the absence of a fall in blood pressure (7). We hypothesized that endotoxemia may be associated with normal blood pressure because of activation of the sympathetic nervous system and renin-angiotensin system (RAS), which secondarily causes renal vasoconstriction.…”
mentioning
confidence: 99%
“…Cytokines, especially TNF-␣ and IL-1, have been shown to be critical mediators of septic shock and ARF (47,48). However, anti-TNF and anti-IL-1 therapies result in little benefit for patients with severe sepsis.…”
Section: Discussionmentioning
confidence: 99%